2016
DOI: 10.21037/jgo.2016.08.13
|View full text |Cite
|
Sign up to set email alerts
|

Beyond HER2: recent advances and future directions in targeted therapies in esophagogastric cancers

Abstract: Esophagogastric cancers (EGCa) are a leading cause of cancer related mortality worldwide. It has been recognized that they represent heterogenous diseases based on histology and anatomy. However, it is also increasingly evident that these are diverse malignancies based on genetic alterations, and this is increasingly making these diseases amenable to targeted therapies. While epidermal growth factor receptor (EGFR) and mTOR inhibitors have failed to prove effective in the treatment of advanced EGCa, vascular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Regulation of angiogenesis requires the participation of a variety of signaling molecules. As a major mediating agent for endothelial cell division, survival, and microvascular permeability regulation, vascular endothelial growth factor (VEGF) receptor 2 (VEGFR-2) together with VEGF is crucial in physiological and pathological angiogenesis 10. Wang et al11 reported that VEGF and VEGFR were highly expressed in squamous cell carcinoma of the esophagus, influencing its development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of angiogenesis requires the participation of a variety of signaling molecules. As a major mediating agent for endothelial cell division, survival, and microvascular permeability regulation, vascular endothelial growth factor (VEGF) receptor 2 (VEGFR-2) together with VEGF is crucial in physiological and pathological angiogenesis 10. Wang et al11 reported that VEGF and VEGFR were highly expressed in squamous cell carcinoma of the esophagus, influencing its development and progression.…”
Section: Discussionmentioning
confidence: 99%